Given J(1, 1), K(3, 1), L(3, -4), and M(1, -4) and that J'(-1, 5), K'(1, 5), L'(1, 0), and M'(-1, 0). What is the rule that tran
anastassius [24]
(x; y) -> (x - 2; y + 4)
J(1; 1) ⇒ J'(1 - 2; 1 + 4) = (-1; 5)
K(3; 1) ⇒ K'(3 - 2; 1 + 4) = (1; 5)
L(3;-4) ⇒ L'(3 - 2; -4 + 4) = (1; 0)
M(1;-4) ⇒ M'(1 - 2;-4 + 4) = (-1; 0)
Answer:
$9.50
Step-by-step explanation:
I took a test on this yesterday and all i know is the answer is either 81 117 or 162
Answer:
Pattern is you add odd numbers, as in 1, 3, 5, 7, 9, etc.
Step-by-step explanation:
11 + 3 = 14
14 + 5 = 19
19 + 7 = 26
26 + 9 = 35
hope this helps